THE INFLUENCE OF CORPORATE GOVERNANCE, LEVERAGE, COMPANY SIZE ON FINANCIAL PERFORMANCE - Yenni Vera Fibriyanti; Mohammad Syafik; Fajriyah Kurnia Laili (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
This study aims to determine the effect of corporate governance as proxied by independent commissioners, directors and audit committees as well as other variables, namely leverage and firm size on financial performance. The data used in this study is secondary data. While the sample in this study is the automotive and component sub-sector manufacturing companies during the 2017-2020 period. The method used is purposive sampling and there are 12 companies included in this research criteria. The results of this study indicate that the independent commissioner variable partially has no effect on financial performance. The directors variable partially has no effect on financial performance. The audit committee variable partially has no effect on financial performance. In the next variable, leverage partially affects financial performance. Firm size variable partially has no effect on financial performance. While the variables of independent commissioners, directors, audit committee leverage, firm size simultaneously affect financial performance.